THE THEORETICAL ASPECTS OF CONSUMER LOYALTY MANAGEMENT IN RESTAURANT ESTABLISHMENTS - Мазуркевич, Ірина; Онищук, Наталя (SWorldJournal, 2024)
This research is devoted to the study of the essence and meaning of consumer loyalty on the example of restaurant enterprises. Special attention is paid to the study of approaches to understanding the essence of loyalty management from the standpoint of a